Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Umkm Di Pusat Grosir Senen Jaya - Livia Yolanda, Yuniarwati (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
This research aimed to examine the effects of tax payers knowledge to Tax Rules in Government Regulation No. 46 Year 2013, the implementation of Self Assessment System, and Tax Penalties of tax compliance among micro, small, and medium enterprises (SMEs) at Pusat Grosir Senen Jaya. This research is a descriptive research and gathered data by distributing questionnaires up to 110 respondents. All data gathered then processed using IBM software SPSS Statistic 23.00 version. The result of this research indicates that all independent variables has a positive effect simultaneously, and all independent variables except for tax penalties have a positive effect partially.